Pengaruh Tipe Pembelajaran dan Minat terhadap Kemampuan Renang Gaya Dada pada Mahasiswa PKLO FIK UNNES - -, Sungkowo (Universitas Negeri Semarang, 2012)
The purpose of ÃÂ research to determine the effect of ÃÂ sintesis learning type, analisis learning type, interest of competence to swimm breast stroke. Subjects were 88 student. The results showed that analisis learning type with mean 71.273 and sintesis learning type type mean 71.636 of competence to swimm breast stroke F = 0,057 < F5% ÃÂ = ÃÂ 3,95 and significantly 0,813 > 0,05. So there is not a difference of significantly. The value of high interest 75.000 and low interest 67.909. The result of value F 21,510 ÃÂ > F tabel = 3,95 with significantly value = 0,000 < 0,05. So there is difference the effect of high interest with low interest. The variables value (AB) of learning type and interest of competence to swimm breast stroke obtained the value F = 0,173 < F5% ÃÂ = 3,95 with significantly ÃÂ 0,678 > 0,05 so there is not interaction of learning type and interest of competence to swimm breast stroke. ÃÂ The result of conclution research is not difference the effect of high interest with low interest. So there is difference the effect of high interest with low interest. There is not interaction of learning type and interest of competence to swimm breast stroke.